Clinical Characteristics and Associated Factors of Colonic Polyps in Acromegaly - Peng, Guiliang; Li, Xing; Zhou, Yuanyuan; Bai, Jianying; Hong, Pian; Li, Weixing; Zhang, Yuling; Zhang, Lei; Liao, Qian; Liao, Mingyu; Zhou, Ling; Sun, Zheng; Shen, Rufei; Zheng, Hongting; Long, Min (Experimental and Clinical Endocrinology & Diabetes, 2022)
Purpose To investigate the clinical characteristics and associated factors of colonic polyps in patients with acromegaly.Methods Clinical characteristics and colonoscopy findings of 86 acromegaly patients who received treatment were retrospectively reviewed, and colonoscopy findings and the correlation with growth hormone (GH)-secreting pituitary adenoma (GHPA) volume and hormonal/metabolic levels were analyzed.Results The prevalence of colonic polyps in acromegaly patients was 40.7% and increased significantly with advanced age, especially in those ≥50 years. Multiple polyps (62.8%) and colonic polyps in the left colon (54.2%) were detected more frequently. Compared to acromegaly patients without polyps, those with polyps displayed higher insulin-like growth factor-1 × upper limit of normal (IGF-1×ULN) levels (P=0.03). IGF-1 levels and GHPA volumes in patients with polyps showed increasing trends, although the differences were not significant. GH levels were higher in patients with polyps of diameter ≤5 mm than those with polyps of diameter >5 mm (P=0.031). The univariate and multivariate logistic regression analysis revealed that GHPA volumes (OR: 1.09, 95% CI: 1.01–1.20; P=0.039) and IGF-1×ULN Q2 levels (OR: 6.51, 95% CI: 1.20–44.60; P=0.038) were independent factors for predicting the risk of colonic polyp occurrence in acromegaly patients. A nomogram was prepared to evaluate the risk of colonic polyps in acromegaly patients.Conclusion The acromegalic patients are a population with a high prevalence of colonic polyps. GHPA volumes and IGF-1×ULN levels may be predictors of colonic polyp occurrence.
Keywords: acromegaly; colonic polyps; growth hormone (GH); colonoscopy; insulin-like growth factor-1(IGF-1)